Acoustic, volumetric and osmotic properties of binary mixtures containing the ionic liquid 1-butyl-3-methylimidazolium dicyanamide mixed with primary and secondary alcohols - Noélia Calvar (2012)
In this paper, densities and speeds of sound for five binary systems {alcohol + 1-butyl-3-methylimidazolium dicyanamide} were measured from T = (293.15 to 323.15) K and atmospheric pressure. From these experimental data, apparent molar volume and apparent molar isentropic compression have been calculated and fitted to a Redlich-Meyer type equation. This fit was also used to calculate the apparent molar volume and apparent molar isentropic compression at infinite dilution for the studied binary mixtures. Moreover, the osmotic and activity coefficients and vapor pressures of these binary mixtures were also determined at T = 323.15 K using the vapor pressure osmometry technique. The experimental osmotic coefficients were correlated using the Extended Pitzer model of Archer. The mean molal activity coefficients and the excess Gibbs free energy for the studied mixtures were calculated from the parameters obtained in the correlation. (c) 2012 Published by Elsevier Ltd.